Cloud-based software services delivery from the perspective of scalability. Issue 2 (4th March 2021) - Al-Said Ahmad, Amro; Andras, Peter
Abstract : Measuring and testing the scalability and performance of cloud-based software services is critical for the delivery of such services, and the development of cloud computing. There are three interconnected Cloud-based software services' performance aspects; both elasticity and efficiency are depending on the delivery of a sufficient level of scalability performance. In this work, we focused on testing and measuring the cloud-based software services scalability from a technical perspective. This paper uses technical scalability metrics that address both volume and quality scaling, inspired by earlier technical metrics of elasticity. We demonstrate the application of the metrics using a practical example and three demand scenarios and discuss the importance of these metrics. We show how our technical scalability metrics integrated into an earlier utility-oriented metric of scalability, in order to enable the scalability analysis from technical and production-driven perspectives. This work is related to the delivery of cloud-based software services from scalability perspective. We demonstrate our metrics by testing a cloud-based software service connecting with both AWS auto-scaling and load-balancing services. Measurements have been collected and analysis, and then been used to calculate the values of our scalability metrics. GRAPHICAL ABSTRACT: